Evaluation of IR Spectral Analysis and Dyeing Parameters for Plasma and /or Nano-Silver Treatments of Polyester and Nylon Fabrics - Ibrahim, Saher Fawzy; Essa, D. M.; Elnagar, Khaled; Abdel-Razik, Ahmed M.; Abdel-Rahman, Adel A.-H (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
In our work of this paper, we study the effect of surface modification of polyester and nylon fabrics induced by DC plasma discharge and/ or nano-siliver treatments .DC plasma discharge was employed at first, as a function of plasma device parameters including different time, different current and different hydrostatic pressure using chemically inert working gas: argon or nitrogen. Optimization of the performance of the applied DC plasma discharge with various applied conditions were performed using Fourier Transform Infra-Red (FTIR) Spectroscopy spectral analysis, by following up the changes in the peak intensity values of the characteristic functional groups that characterize polyester fabric. Then the dyeing properties of different pretreated fabrics with plasma by the best conditions are subjected to nano-silver treatment by concentration 50 ppm under the effect of different dye concentrations, different dyeing temperature and different dyeing time. Finally, the fastness properties to light and washing for the treated samples were studied. The results obtained showed that both of the dyeing parameters and fastness properties were highly improved by the treatment of fabrics by either individual plasma treatment or combined DC cold plasma and nano-silver treatments.